Improving Local Sustainability in Manufacturing Industri: A benchmarking study - Gunnarsson, Isak; Göransson, Petra (My University, 2023)
We would like to express our sincere gratitude to Hilti Svenska AB for providing us the opportunity to conduct our master thesis in collaboration with their organization. We are truly grateful for their support, resources, and the valuable insights they shared throughout the project. We extend a special thanks to our supervisor at Hilti Svenska AB, Sofia Blidberg, for her guidance, expertise, and continuous support. Her invaluable inputs, encouragement and passion for sustainability have been instrumental for this project. We would also like to acknowledge and express our deep appreciation to our supervisor at Chalmers University of Technology, Mélanie Despeisse. Her extensive knowledge, guidance, and constructive feedback have been crucial in steering our research in the right direction and ensuring its academic rigor. Furthermore, we extend our thanks to our examiner, Cecilia Berlin, for her time and valuable feedback during the evaluation of our work. We appreciate her thorough review and insightful suggestions, which have helped strengthen the overall quality of our thesis. Finally, thanks to friends, families, and fellow students who, directly or indirectly, have supported us during our years at Chalmers University of Technology.